Autism as emergent and transactional - Green, Jonathan (Frontiers in Psychiatry, 2022)
The current epistemology of autism as a phenotype derives from the consistency of historical accounts and decades of work within the tradition of descriptive epidemiology, culminating in current categorical descriptions. The demonstrated high heritability of the phenotype has led to an essentialist theory of autism as a biological entity, and in the concerted search within developmental brain and genetic science for discrete biological markers. This search has not revealed simple markers, and has led to moves towards a more dimensional account. This paper proposes an alternative transactional approach to understanding autistic states as an emergent property within a complex system, as the neurodiverse brain and mind encounters their social and physical environment within early development. Evidence supporting this approach comes from intervention trials based on a developmental transactional account; both in the infancy pre-diagnostic prodrome and the early post diagnostic period. These intervention trials show that the emergence and continuity of the prototypical autistic phenotype is to a degree malleable to altered targeted changes in the social environment of the child. Such a transactional approach enlarges our notion of the phenotype and brings the study of autism into mainstream individual difference developmental science. It challenges essentialist views, for instance as to intrinsic autistic ‘social avoidance’ and is consistent with the lived experience of autistics and their advocacy for improved understanding within a social model.